Manual of peripheral nerve surgery from the basics to complex procedures - Socolovsky, Mariano; Rasulic, Lukas; Midha, Rajiv; Garozzo, Debora (Thieme, 2018)
Developed and written by top international experts in the field, this lucid new work is a comprehensive yet concise manual for reviewing the basics of peripheral nerve anatomy, pathophysiology, all typical and classic lesions, and the appropriate diagnostics. The chapters culminate in a description of the complex step-by-step surgical repair of these lesions.